The Effect of DER and ROA on Stock Price with EPS as Mediation in Industrial Companies - Syam, Muhammad Raihan; Lestari, Wuryaningsih Dwi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The stock market in Indonesia is not just a number that can rise and fall without meaning. It's a one of key element of the national economy that has a huge impact on the lives of millions of people. Used to develop businesses, which in turn drives economic growth and improves people's welfare. Methodology: This research employs quantitative methods, utilizing a non-probability sampling approach specifically through purposive sampling. The data collection process collecting, recording, and reviewing secondary data in the form of financial statements of companies registered at IDX. Results of which obtained 39 industrial companies and using panel data analysis and sobel test with Eviews 12 for analysis tool. Results: This study finds that DER and ROA significantly influence stock prices but EPS did not effect on stock price, while EPS as a mediating variable between ROA and DER also did not mediate the relationship between stock prices. Applications/Originality/Value: These findings provide valuable insights for investors and policymakers in understanding the factors driving stock price movements and making informed investment decisions. The higher earnings per share does not affect the stock price, so investors are more interested in putting money into the company because they can't focus on one object.